TINJAUAN HUKUM BIDANG PEMBINAAN DAN PENGAMANAN TERHADAP ANGGOTA POLRI YANG MELAKUKAN PENYALAHGUNAAN NARKOBA BERDASARKAN PERATURAN PEMERINTAH RI NOMOR 2 TAHUN 2003 TENTANG PERATURAN DISIPLIN ANGGOTA POLRI - Abdul Rokhim, Aulia Tohari dan (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
This study aims to determine criminal liability before entering generalcriminal acts against members of the national police who commit drugabuse and to find out the process of sentencing against members of thenational police who commit drug abuse.The criminal act of narcotics abuse committed by members of theIndonesian National Police is also a violation of disciplinary regulationsand the Polri Professional Code of Ethics, therefore Article 12 paragraph(1) of Government Regulation Number 2 of 2003 concerning DisciplinaryRegulations of Members of the Indonesian National Police confirms that"Imposition of disciplinary punishment not delete criminal charges ".In handling criminal sanctions against police officers who abuse narcoticsLaw No. 35 of 2009 concerning Narcotics. The provisions do not onlyapply to members of the police force but also to other communities whohave been proven to have abused narcotics. Narcotics criminal provisions(forms of criminal acts committed and the threat of criminal sanctions forthe perpetrators) are regulated in Law No. 35 of 2009 listed in severalarticles. These articles include Article 111 - Article 127, Article 129 andArticle 137